Final Report on Understandings of Interdisciplinary and Transdisciplinary Research and Factors of Success and Failure - Vienni Baptista, Bianca; Fletcher, Isabel; Maryl, Maciej; Wciślik, Piotr; Buchner, Anna; Lyall, Catherine; Spaapen, Jack; Pohl, Christian (My University, 2020)
This report presents findings from a literature review and survey undertaken as part of the SHAPE-ID Horizon 2020 project (https://www.shapeid.eu), which addresses the challenge of improving interdisciplinary research (IDR) and transdisciplinary research (TDR) between Arts, Humanities and Social Sciences (AHSS) and Science, Technology, Engineering, Mathematics, and Medicine (STEMM) disciplines. One of SHAPE-ID’s first objectives was to review existing research on IDR/TDR. Through an extensive evidence-scanning exercise drawing on previous work undertaken and complemented by a survey and interviews, the project aimed: (i) to disentangle the different understandings of interdisciplinarity and transdisciplinarity; (ii) to identify the factors that hinder or help inter- and transdisciplinary collaboration; (iii) to clarify which understandings of IDR/TDR and which factors of success and failure are specifically relevant for integrating AHSS in IDR/TDR.
Acknowledgments: The team wants to specially thank: Dr. Sabine Hoffmann (Swiss Federal Institute of Aquatic Science and Technology, EAWAG, Switzerland), Professor em. Julie Thompson Klein, and Dr. Flurina Schneider (Centre for Development and Environment, University of Bern, Switzerland) for their support and input in different phases of the study. We are grateful to the OpenAire team (Harry Dimitropoulos and Claudio Atzori) for providing the metadata for the analysis and to Poznań Supercomputing and Networking Center (Juliusz Pukacki and Cezary Mazurek) for providing the virtual R-Studio machine capable of crunching data analysed in this project.
Keywords: Interdisciplinarity; transdisciplinarity; interdisciplinary research; transdisciplinary research; arts; humanities; social sciences; integration; research policy; research funding; science policy; factors success; factors failure; understandings; International Integration; Interdisciplinary research; RESEARCH POLICY IMPLICATIONS; interdisciplinary collaboration; transdisciplinary collaboration